Nigerian Pidgin as a Vehicle for Social Reconstruction in the Poetry of Akachi Adimora-Ezeigbo - Odey , Josephat Adoga; Uwen , God’sgift Ogban; Ogar, Patrick Odey (International Journal of Arts, Languages, Linguistics and Literary Studies, 2022)
The indebtedness of the African poets to oral tradition and its connectedness with the anxieties of contemporary realities cannot be overemphasized. This paper on “Nigerian Pidgin as a Vehicle for Social Reconstruction in the Poetry of Akachi Adimora-Ezeigbo” interrogates the plights of the masses artistically weaved in poetic riddles, proverbs, and allusions to rehearse African oral tradition and its impact on the socio-political realities, particularly in Nigeria. This study re-echoes Isidore Okpewho’s earlier stand that most African poets absolve themselves from the influence of the colonial experience on the African culture, although it is admitted in contemporary works of the shifted towards the re-rooting with Africanness for self-discovery towards the exposition of social realities. Adimora-Ezeigbo tows the latter’s path and borrows from the myth and belief system of Africa to propagate her ideological and idolized disposition in written form. Her poems in Nigerian Pidgin re-echo orality as an unswerving source of literary exploitation in Nigerian post-colony. Relying on the conceptualizations of Marxism, the study concludes that spoken words preserved in written form directly communicates to our thoughts and emotions while yearning for change. In the selected poems from Heart Songs and Dancing Masks, Adimora-Ezeigbo efficiently appropriates the use of the classless linguistic form as a veritable tool to ignite the consciousness of the complacent driven people and the “I don’t care” attitude of the leaders in the Nigerian society.